Bullous pemphigoid and radiotherapy: case report and literature review update - Antonio Piras; Bruno Fionda; Antonella Sanfratello; Andrea D'Aviero; Giovanni Sortino; Gianfranco Pernice; Luca Boldrini; Tommaso Angileri; Antonino Daidone (PAGEPress Publications, 2021)
INTROUDCTION Bullous pemphigoid (BP) is a common autoimmune bullous disease generally occurring in elderly patients. Itchy and tense blisters on normal skin or erythematous and edematous lesions on the trunk and extremities usually characterize BP. Trigger factors are still unclear while several case reports suggest a potential role of radiotherapy (RT) as BP trigger for disease onset or recrudescence. A review was performed in order to provide an update of literature. A case report of a patient affected by BP undergoing two radiotherapy courses for a primary breast cancer was also reported. MATERIALS AND METHODS A comprehensive review of the published literature was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. The review included studies describing BP and its relationships with RT treatments. RESULTS A total of 13 articles were reviewed. Studies characteristics analysis resulted in eleven case reports, one case series and one large-scale case-control study. CONCLUSIONS Literature update confirms the existence of a reasonable connection between RT and BP. Case report showed that a multidisciplinary management seems to assure the feasibility of RT in patients affected by BP, not depriving them of standard therapeutic opportunities.